Epigenetic modifications preserve the hyperaccumulator Noccaea caerulescens from Ni geno‐toxicity. (15th April 2018) - Gullì, Mariolina; Marchi, Laura; Fragni, Rosaria; Buschini, Annamaria; Visioli, Giovanna
Abstract : The Ni hyperaccumulator Noccaea caerulescens has adapted to live in a naturally stressed environment, evolving a complex pattern of traits to cope with adverse conditions. Evidence is accumulating regarding the important role of epigenetic modifications in regulating plant responses to stress. In this study, we present data from the natural "open‐field" adaptation of the Ni hyperaccumulator N. caerulescens to serpentine soil and provide the first evidence of the involvement of epigenetic changes in response to the high Ni content present in plant leaves. The alkaline comet assay revealed the integrity of the nuclei of leaf cells of N. caerulescens grown in a Ni‐rich environment, while in the non‐tolerant Arabidopsis thaliana exposed to Ni, the nuclei were severely damaged. DNA of N. caerulescens plants grown in situ were considerably hyper‐methylated compared to A. thaliana plants exposed to Ni. In addition, qRT‐PCR revealed that N. caerulescens MET1, DRM2, and HDA8 genes involved in epigenetic DNA and histone modification were up‐regulated in the presence of high Ni content in leaves. Such epigenetic modifications may constitute a defense strategy that prevents genome instability and direct damage to the DNA structure by Ni ion, enabling plants to survive in an extreme environment. Further studies will be necessary to analyze in detail the involvement of DNA methylation and other epigenetic mechanisms in the complex process of metal hyperaccumulation and plants' adaptive response. Environ. Mol. Mutagen. 59:464–475, 2018. © 2018 Wiley Periodicals, Inc.